Стан толерантності до фізичного навантаження у хворих на цукровий діабет і його значення в медико-соціальній експертизі та медичній реабілітації - Вернигородська, М. В.; Забур'янова, В. Ю.; Вернигородський, В. С. (Clinical Endocrinology and Endocrine Surgery, 2012)
The article presents the study of determining the state of exercise tolerance in patients with diabetes mellitus type 1 and 2 using the bicycle exercise test. We prove that the test with dosed physical load in patients with diabetes is necessary to determine the physical condition and level of physical fitness to improve medico-social expertize and planning of physical exercise, reduction of blood glucose levels and preventing cardiovascular complications.